Cartilaginous Choristoma of the Gingiva: A Rare Clinical Entity - Ramalingam Suganya; Narasimhan Malathi; Subramani Vijaya Nirmala; Chinnaswami Ravindran; Harikrishnan Thamizhchelvan (Case Reports in Dentistry)
Choristomas are rare entities which are aggregates of microscopically normal cells or tissues in aberrant locations. They are a “heterotopic” rest of cells, as they appear as a tumor-like mass. Herein we report a case of cartilaginous choristoma in a 54-year-old male who presented with a swelling on right lower gingiva. The histopathological examination revealed features of a well circumscribed mass of mature cartilage in a dense fibrous connective tissue stroma.